Brachytrupes megacephalus Lefèbvre, 1827 (Orthoptera, Gryllidae) in the Maltese Islands: notes on biogeography, behaviour, and habitat of populations in the central Mediterranean area and the Maghreb - Cassar, Louis F.; Conrad, Elisabeth; Galdies, Charles (Zootaxa, 2021)
Brachytrupes megacephalus (Lefebvre, 1827) is of significant biogeographic importance. It occurs in Sicily and on some of the circum-Sicilian and Pelagian islands, as well as in the Maltese Islands, Sardinia and the Maghreb (notably but not exclusively, in Algeria and Tunisia, where it maintains populations in both coastal and desert regions). Within European territory, it occurs solely in Italy and Malta, where it is protected under the EU Habitats Directive and the Bern Convention. In northern Africa, the species is regarded as a polyphagous pest, particularly in Saharan locations. The present work is based on field observations, mostly from the Maltese Islands, that span more than three decades; it provides insights on spatial distribution, population trends and behaviour. In examining the relationship between the species’ frequency during its mating season and weather conditions, results suggest a weak yet statistically significant correlation between mating strategies and ambient meteorological conditions. Moreover, patch occupancy in spring and autumn varied considerably within a specified area of study, primarily due to competitive mating strategies employed in spring, with an occupancy ratio of approximately 1:6. To-date, the species is known from 13 locations, one in Gozo and 12 in Malta, of which some constitute the Ahrax promontory metapopulation. Connectivity between the Ahrax subpopulation cluster is discussed in the light of habitat and topographical characteristics. Contrasting findings on variances in behaviour between Maltese populations and other populations in Sicily and the Maghreb are discussed. Discernible behavioural disparities include the length of excavated tunnels during spring and summer/autumn seasons in the different geographical locations, attraction to artificial sources of light, and the degree of damage to crops across geographic regions.